New Modified AODV for MANET (International Journal of Engineering and Computer Science, 2017)
Mobile Communication is a wireless connection between two nodes which is having limited bandwidth and high rate of data disconnnection. So there is a requirement of new MANET routing protocol having low rate message overhead. Hence it is necessary to enhancement the performance of MANET. The reduction of routing overhead decreases the usage of bandwidth of the network. The increase of bandwidth will increase the throught and decrease the latency of the nodes of the network. This Paper proposes the new Routing Protocol which will increase the throughput,reliability and decrease the latency of the network. 1. Introduction:The mobile adhoc network[1] does not have any fixed infrastructure and base station of the network and thats why the name is used.There are many applications for ad-hoc networks like conferencing, emergency services, personal area networks, embedded computing, and sensor dust. A MANET is a network that allows direct communication of two nodes, when radio propagation conditions exist between two nodes. If there is no direct connection between the source and the sink nodes, multi-hop routing is used. In multi-hop routing, a packet is forwarded from one node to another, until it reaches the destination. A routing protocol is necessary in adhoc networks; this routing protocol has to adapt quickly to the frequent changes in the adhoc network topology. Ad-hoc routing protocols are classified into three categories. The first category is Table-driven (Proactive) routing protocols such as DSDV [2], CGSR [3], GSR [4], FSR [5], and OLSR [6]. The second category is on-demand (Reactive) routing protocols such as AODV [7], DSR [8], ABR [9], SSA [10], and TORA [11]. The third category is Hybrid (Reactive and proactive) routing protocols such as ZRP [12] and ZHLS [13].